Influence of cosubstrate concentration on xylose conversion by recombinant, XYL1-expressing Saccharomyces cerevisiae: a comparison of different sugars and ethanol as cosubstrates. - Meinander, N Q (1997)
Conversion of xylose to xylitol by recombinant Saccharomyces cerevisiae expressing the XYL1 gene, encoding xylose reductase, was investigated by using different cosubstrates as generators of reduced cofactors. The effect of a pulse addition of the cosubstrate on xylose conversion in cosubstrate-limited fed-batch cultivation was studied. Glucose, mannose, and fructose, which are transported with high affinity by the same transport system as is xylose, inhibited xylose conversion by 99, 77, and 78%, respectively, reflecting competitive inhibition of xylose transport. Pulse addition of maltose, which is transported by a specific transport system, did not inhibit xylose conversion. Pulse addition of galactose, which is also transported by a specific transporter, inhibited xylose conversion by 51%, in accordance with noncompetitive inhibition between the galactose and glucose/ xylose transport systems. Pulse addition of ethanol inhibited xylose conversion by 15%, explained by inhibition of xylose transport through interference with the hydrophobic regions of the cell membrane. The xylitol yields on the different cosubstrates varied widely. Galactose gave the highest xylitol yield, 5.6 times higher than that for glucose. The difference in redox metabolism of glucose and galactose was suggested to enhance the availability of reduced cofactors for xylose reduction with galactose. The differences in xylitol yield observed between some of the other sugars may also reflect differences in redox metabolism. With all cosubstrates, the xylitol yield was higher under cosubstrate limitation than with cosubstrate excess.